2012
DOI: 10.7324/japs.2012.21103
|View full text |Cite
|
Sign up to set email alerts
|

What Are The Effects of Silibinin on Testicular Tissue of Mice?

Abstract: Silibinin (silybin) is one of the structural isomers of the flavonoid silymarin, and it has wide variety of phytotherapeutic applications and the aim of this study was to investigate the effects of different doses of silibinin on testicular tissue of mice. Twenty male Swiss albino mice were divided into four groups. Each group consist of five animal, (Group 1) (negative control) animals were administered single intraperitoneal (IP) daily dose of phosphate buffer for 5 days, Groups (2, 3, and 4) were given a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is well known that nickel has various carcinogenic effects on internal organs such as the liver, kidneys and lungs, and a toxic effect on the immune system, genes, blood, nervous system, and reproductive system (Das et al 2008). Several studies have shown the harmful effects of nickel on testicular tissue (Doreswamy et al 2004, Oufi et al 2012. On the basis of the results obtained with the histopathological and immunohistochemical staining of the testicular tissues of Group 4 it was concluded that SB had a protective effect against the adverse effects of nickel sulfate.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is well known that nickel has various carcinogenic effects on internal organs such as the liver, kidneys and lungs, and a toxic effect on the immune system, genes, blood, nervous system, and reproductive system (Das et al 2008). Several studies have shown the harmful effects of nickel on testicular tissue (Doreswamy et al 2004, Oufi et al 2012. On the basis of the results obtained with the histopathological and immunohistochemical staining of the testicular tissues of Group 4 it was concluded that SB had a protective effect against the adverse effects of nickel sulfate.…”
Section: Discussionmentioning
confidence: 93%
“…Lukac et al (2014), reported that a single intraperitoneal dose of nickel chloride reduced sperm motility and concentration in adult male mice. Oufi et al (2012) determined that, when administered to mice at several different doses, SB reduced the number of nonviable sperm and improved sperm motility, and also observed that the percentage of abnormal spermatozoa decreased. Similarly, in the present study, in Group 4 it was ascertained that SB had a protective effect against the adverse effects of nickel on sperm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, due to the silymarin antioxidant activity and capacity to defend plasma lipids from oxidation, silymarin was shown to significantly alter the experimental groups ( Thomas et al, 1997 ). A previous study ( Oufi et al, 2012 ) focused on the effect of silybin (One of the structural isoforms of silymarin is silybin) on testicular tissue and proved that this flavonoid can improve testicular parameters such as the diameter of the primary spermatocytes and spermatids, motility of sperm, and percentage of live sperm. In addition, silymarin increased testosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…So, an increased MDA level is considered an important indicator of lipid peroxidation and subsequently, loss of membrane structures and functions. Testes, rich in PUFA and having high metabolism rates and cell replication and poor antioxidant defenses, are much more vulnerable to peroxidation injury than other tissues [41] . Increased MDA levels in rat testes following TAA exposure were similarly reported in previous studies [42] .…”
Section: Leydig Cell Number Was Negatively Correlated Withmentioning
confidence: 99%